Antimicrobial therapy and bacterial resistance: a pilot survey - Abdullah, A. Salam; Baggot, J. Desmond; Too, H. L. (Malaysian Society of Applied Biology, 1986)
It was only about 40 years ago that tuberculosis, cholera, scarlet fever, syphilis and pneumonia, which were the leading infectious diseases causing death on a worldwide basis were effectively treated with antibiotics. Since that time the frequent and often indiscriminate use of antimicrobial agents in medical practice, both human and veterinary, has resulted in the widespread development of bacterial resistance. Transferable drug resistance factors were first demonstrated in Shigella by Ochiai et al. (1959) and independently by Akiba et al. (1960). Over the years it has repeatedly been inferred, often without conclusive evidence, that resistance bacteria originating from food-producing animals were responsible for sudden outbreaks of "difficult to treat" infections in humans. AI. though the extent to which this is true cannot be determined, it is generally accepted that resistant bacterial strains of animal origin can reach humans in contaminated food products. It is strongly suspected that the use of antibiotics as growth promotants, given continuously in the feed, has facilitated the development of resistant bacterial strains in farm animals. Two independent studies carried out in preantibiotic communities have presented evidence that R factor evolved before the advent of the antibiotic era (Davis and Anandan, 1970; Gardner et al., 1969). This interesting finding does not diminish the contribution of frequent antibiotic usage to the development of bacterial resistance.